Use of the AO Wire Passer to Aid Placement of Obstetrical Saw Wire for Osteotomy - Cockshutt, Joanne R.; Gofton, N. (Veterinary and Comparative Orthopaedics and Traumatology, 1994)
The AO wire passer can be used as an effective guide for passage of obstetrical saw wire for osteotomy. Use of the wire saw and passer reduces soft tissue trauma by minimizing tissue dissection, and promoting positioning of the saw in close contact with the bone.
Keywords: Instrumentation; osteotomy; Gigli saw